Cochrane Database of Systematic Reviews 2005
DOI: 10.1002/14651858.cd003879.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating asymptomatic impacted wisdom teeth in adolescents and adults

Abstract: Notes This trial has been stopped this year (2004). At this moment the reason has not been communicated to the reviewers 13 Interventions for treating asymptomatic impacted wisdom teeth in adolescents and adults (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 16 publications
0
62
0
10
Order By: Relevance
“…Despite this conclusion, the Cochrane Oral Health Group systematic review conducted in 2005 found no evidence to support or to refute the prophylactic removal of impacted wisdom teeth. 7 It would be ideal if health managers (and the clinician!) could somehow know exactly which teeth will cause problems in We now know that the development of symptoms associated with these teeth is no longer completely due to chance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this conclusion, the Cochrane Oral Health Group systematic review conducted in 2005 found no evidence to support or to refute the prophylactic removal of impacted wisdom teeth. 7 It would be ideal if health managers (and the clinician!) could somehow know exactly which teeth will cause problems in We now know that the development of symptoms associated with these teeth is no longer completely due to chance.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005 a Cochrane Oral Health Group systematic review found no evidence to support or to refute the prophylactic removal of impacted wisdom teeth. 7 The main clinically relevant questions are: 'What percentage of pathologyfree impacted third molars will remain free of disease if retained?' and 'How can we predict the likelihood of development of disease in these teeth?…”
Section: Introductionmentioning
confidence: 99%
“…D'après de nombreux auteurs le bénéfice maximal de l'extraction des dents de sagesse concerne les patients jeunes du fait notamment de suites opé-ratoires plus favorables [4,7,68] . Le risque de complication des extractions est évalué par Crosse [19] à 12 % chez les 12-29 ans et à 22 % chez les 25-81 ans.…”
Section: Les Bénéfices Liés à L'avulsion Précoce Des Dents De Sagesseunclassified
“…Au total l'évaluation du rapport bénéfices/risques de l'extraction de dents de sagesse asymptomatiques est délicate. Dans le cadre d'une revue systématique d'études contrôlées randomisées effectuées au profit du Cochrane collaboration [93] , les auteurs n'ont trouvé aucune preuve permettant de soutenir ou au contraire de réfuter la pratique consistant à extraire des dents de sagesse asymptomatiques.…”
Section: Limites Des Publicationsunclassified
“…They also noted that the methodological quality of the literature reviews was generally poor and none of the reviews was systematic [8]. Mettes et al [9] also showed no evidence to support nor refute regular prophylactic removal of asymptomatic impacted third molars in adults. They also found prophylactic removal of asymptomatic impacted third molars in adolescents neither reduces nor prevents late incisor crowding.…”
Section: Introductionmentioning
confidence: 99%